(untitled) (Global Journal of Science Frontier Research, 2021)
Application in the unipolar engines of samarium-cobalt magnets opens the new prospects of creating the engines, with the large rotational moment, since. such magnets possess the great magnetic field, which cannot they will reach in other magnets. However, the creation of engines with the large diameter of disk runs into the great difficulties connected with the fact that industry does not let out magnets with the large diameter. In the article is proposed the new construction of unipolar engine, in which for creating the magnetic field are used the magnets of small diameter.